Strategi Penatalayanan Gereja Dalam Menghadapi Tantangan Globalisasi - Waruwu, Nofedin; Ardiyanto, Yudha; Pandie, Remegises Danial Yohanis; Sakaro Situmorang, Juandi (Pusat Studi Pentakosta Indonesia, 2024)
This study also aims to improve the congregation's understanding of the importance of stewardshipand how they can play an active role in supporting church ministry. In practice, many churches face major challenges in carrying out stewardship in accordance with biblical principles. These challenges can stem from a variety of factors, including a lack of in-depth understanding of stewardship, limited resources, and a lack of congregational involvement and participation in church management.This article was written using a literature study method.The application of good stewardship principles has a positive impact on the growth of the congregation, both spiritually and physically. Effective stewardship can increase congregational participation in church activities, strengthen relationships between congregations, and support the development of various ministries in the church. In addition, good resource management also allows the church to be more responsive to the needs of the congregation and the surrounding community. Today's church needs to develop a contextual and relevant stewardship model that can answer challenges and take advantage of existing opportunities. Stewardship models based on congregational participation, technology, servant leadership, contextual needs, and community are some approaches that can be considered to increase the effectiveness of stewardship in the church.Abstrak